KONSEP MODERAT YUSUF QARDHAWI: - Ahmad Dumyathi Bashori (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2013)
Yusuf Qardhawi is one of prominent Islamic cleric as moderate figure. It is reflected from his ideas and thoughts both in his books and religious speeches. This article explores the reasons why Yusuf Qardhawi was deemed as icon of moderate Islam and also reveals his the standards of moderate. Moderate attitudes, of course, come from the way one understand the sacred text (Qur’an). In this matter, Yusuf Qaradhawi argues the way muslims should understand the nash.